(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Ordinary Portland cement (OPC) is used as the primary binder to produce concrete. The amount of the CO₂ released during the manufacture of OPC is in the order of one ton for every ton of OPC produced. Attempts made to reduce the use of OPC in concrete are receiving much attention due to environment related issues. In the present study marble dust is used as a partial replacement for cement. It has been estimated that several million tons of Marble Dust are produced worldwide from extracting to finishing process. Hence its utilization has become an important alternative material because of its cement like properties. Marble dust is also easily available at very less cost. Concrete is characterized by quasi-brittle failure i.e; once failure is initiated; nearly complete loss of loading capacity takes place. By addition of randomly distributed fibers in the concrete matrix concrete can be modified to perform in a more ductile manner which prevent and control initiation, propagation and coalescence of cracks. The fibers prevent surface cracking through bridging action leading to an increased resistance of the concrete. This paper presents results of an experimental program to determine mechanical properties of concrete as cement is replaced with marble dust with known percentages (0%, 5%, 10%, 15%) [5] [6] for the grade of M30 and addition of polypropylene fibers of different percentage (0%, 0.5%, 1%, and 1.5%). The concrete test samples were submitted to compressive strength tests after 7 and 28 days of moist curing, as well as flexure and splitting tensile strength tests. Overall Strength of Concrete (Compressive, Tensile & Flexure) showed a reasonable increase upto a limit of 10% for Marble Dust and 0.5% for PP Fibers [1].